2013
DOI: 10.1051/0004-6361/201220801
|View full text |Cite
|
Sign up to set email alerts
|

NoSOCS in SDSS

Abstract: Context. We investigate relations between the color and luminosity distributions of cluster galaxies and the evolutionary state of their host clusters. Aims. Our aim is to explore some aspects of cluster galaxy evolution and the dynamical state of clusters as two sides of the same process. Methods. We used 10 721 member galaxies of 183 clusters extracted from the Sloan Digital Sky Survey using a list of NoSOCS and CIRS targets. First, we classified the clusters into two categories, Gaussian and non-Gaussian, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 105 publications
6
42
0
Order By: Relevance
“…Specifically, if we split our sample into two redshift bins at z=0.45-which optimally balances the number of bright galaxies in the high and low bins-we see the strong drop in peculiar velocity for bright galaxies in each of the high and low-redshift bins. This same qualitative effect has been observed in lowredshift clusters (Chincarini & Rood 1977;Biviano et al 1992;Mohr et al 1996;Goto 2005;Old et al 2013;Ribeiro et al 2013). Barsanti et al (2016) also recently observed a similar effect in an analysis of galaxy clusters drawn from the literature.…”
Section: Velocity Segregation By Relative Luminositysupporting
confidence: 73%
“…Specifically, if we split our sample into two redshift bins at z=0.45-which optimally balances the number of bright galaxies in the high and low bins-we see the strong drop in peculiar velocity for bright galaxies in each of the high and low-redshift bins. This same qualitative effect has been observed in lowredshift clusters (Chincarini & Rood 1977;Biviano et al 1992;Mohr et al 1996;Goto 2005;Old et al 2013;Ribeiro et al 2013). Barsanti et al (2016) also recently observed a similar effect in an analysis of galaxy clusters drawn from the literature.…”
Section: Velocity Segregation By Relative Luminositysupporting
confidence: 73%
“…Adami et al (1998) and Ribeiro et al (2013) both found VLS for ellipticals and passive galaxies, but no (or even opposite) effect is reported for galaxies of other types. However, the inspection of Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, in multicomponent clusters, we find that these correlations are still preserved. Indeed, Ribeiro et al (2013) find a decreasing fraction of red galaxies with distance from the centers of both Gaussian and non-Gaussian clusters.…”
Section: Star Formation In Single-and Multi-component Clustersmentioning
confidence: 94%